MANAJEMEN MUTU TERPADU (MMT) DALAM PENDIDIKAN ISLAM - Mulyadi Hermanto Nasution (Universitas Muhammadiyah Tapanuli Selatan, 2019)
The principle of management is the overall supervision of all members of educational institutions of the Organization's activities. The implementation of Total Quality Management (TQM) means that all school members are responsible for the quality of education, so all parties involved in the academic process in Islamic educational institutions, ranging from school / madrasah committees, principals / madrasas, heads of administration, teachers, students to with employees must truly understand the nature and purpose of this education. In other words, each individual involved must understand what the goals of education are. Without a thorough understanding of the individuals involved, it is not possible to apply TQM.This management system greatly minimizes the bureaucratic process. A bureaucratic system of Islamic educational institutions will hamper the potential development of the institution itself. The problems that I want to discuss in this Paper are: 1) What is meant by Integrated Quality Management (MMT) ?; 2) What Are the Principles and Advantages of Integrated Quality Management (MMT) in Islamic Education ?; 3) What is the implementation of TQM and indicators of success in Islamic education? So from the problem that the author chose, the purpose of writing this paper is: Explaining the understanding of Integrated Quality Management (TQM), Explaining the Principles and Advantages of TQM in Islamic Education and Identifying indicators - indicators of successful implementation of TQM in the field of Islamic educationKeywords: Total Quality ManagementAbstrak